UPAYA DALAM MENGURANGI ABSENTEEISME TENAGA PERAWAT PADA ORGANISASI KERJA (Efforts To Reduce Nursing Absenteeism On Work Organization) - Mastuty, Amalia; Paju, Wanto (JURNAL NERS LENTERA, 2018)
Background: The absence or absenteeism of the nurses results in the loss of working time to complete the task so that the work that should be completed within a certain period of time becomes abandoned. This will indirectly cause harm to nurses and for hospitals both in terms of material and the applicable system. In general, abseenteism and lost working hours in 12% of American hospitals are absent, in Indonesia ranging from 3% -10% of them Puskemas in Papua 30.7% are absent, in Bekasi Hospital 93.20% arriving late, at Semarang Hospital 4.3% nurses were absent. Objectives: To identify the identification of effective interventions that assist management in reducing absenteeism of nurses and improving work productivity. Methods: Literature searches from 2009-2017 using keyword reducing absenteeism and Nurse. Search were done on the Ebscohost, Elsevier and Google Sholar sites. From the search results obtained as many as thirteen journals related to the theme. Results: a study of thirtee literatures found that to reduce absenteeism of nurses is by providing social support, implementing six staff organizing strategies, leadership approaches as well as increasing extrinsic motivation in work organization